POSITIVE study: physical exercise program in non-operable lung cancer patients undergoing palliative treatment. Issue 1 (December 2016) - Wiskemann, Joachim; Hummler, Simone; Diepold, Christina; Keil, Melanie; Abel, Ulrich; Steindorf, Karen; Beckhove, Philipp; Ulrich, Cornelia; Steins, Martin; Thomas, Michael
Abstract Background Patients with advanced stage non-small cell lung cancer (NSCLC) or small cell lung cancer (SCLC) often experience multidimensional impairments, affecting quality of life during their course of disease. In lung cancer patients with operable disease, several studies have shown that exercise has a positive impact on quality of life and physical functioning. There is limited evidence regarding efficacy for advanced lung cancer patients undergoing palliative treatment. Therefore, the POSITIVE study aims to evaluate the benefit of a 24-week exercise intervention during palliative treatment in a randomized controlled setting. Methods/design The POSITIVE study is a randomized, controlled trial investigating the effects of a 24-week exercise intervention during palliative treatment on quality of life, physical performance and immune function in advanced, non-operable lung cancer patients. 250 patients will be recruited in the Clinic for Thoracic Diseases in Heidelberg, enrolment begun in November 2013. Main inclusion criterion is histologically confirmed NSCLC (stage IIIa, IIIb, IV) or SCLC (Limited Disease-SCLC, Extensive Disease-SCLC) not amenable to surgery. Patients are randomized into two groups. Both groups receive weekly care management phone calls (CMPCs) with the goal to assess symptoms and side effects. Additionally, one group receives a combined resistance and endurance training (3x/week). Primary endpoints are quality of life assessed by the Functional Assessment of Cancer Therapy for patients with lung cancer (FACT-L, subcategory Physical Well-Being) and General Fatigue measured by the Multidimensional Fatigue Inventory (MFI-20). Secondary endpoints are physical performance (maximal voluntary isometric contraction, 6-min walk distance), psychosocial (depression and anxiety) and immunological parameters and overall survival. Discussion The aim of the POSITIVE trial is the evaluation of effects of a 24-week structured and guided exercise intervention during palliative treatment stages. Analysis of various outcomes (such as quality of life, physical performance, self-efficacy, psychosocial and immunological parameters) will contribute to a better understanding of the potential of exercise in advanced lung cancer patients. In contrast to other studies with advanced oncological patients the POSITIVE trial provides weekly phone calls to support patients both in the intervention and control group and to segregate the impact of physical activity on quality of life. Trial registration ClinicalTrials.govNCT02055508 (Date: December 12, 2013)